DEMOGRAPHIC DETERMINANTS OF RELATIONAL AGGRESSION AMONG ADOLESCENT STUDENTS: Relational Aggression - Riaz, Saima; Bano, Zaqia; Anjum, Razia; Ansari, Sami Ul Haque (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the predictive relation of demographic variables with relational aggression.Study Design: Cross sectional study.Place and Duration of Study: Department of Psychology, University of Gujrat, Gujrat Pakistan, from Aug 2017 to Jan 2018.Methodology: A total of 612 adolescent students were selected with age 12-19 years from diverse academic institutes of Gujrat city. Urdu version of diverse adolescent relational aggression scale was used to measure relational aggression. Neural network analysis was carried out by using SPSS-21.Result: The findings of this study revealed significant predictive relation of demographic variables (gender, birth order, family system, number of siblings and age) with relational aggression. The most important predictor of relational aggression in teenagers was birth order 0.249 (100%), age 0.246 (98.9%) siblings 0.242 (86.3%), family system 0.166 (66.8%) and gender 123 (49.6) respectively.Conclusion: Demographic variables are the significant predictor of relational aggression. By managing the effects of these variables, adverse behavior of relational aggression can be controlled in adolescent students